Systematic review of locking solutions for non‐tunneled hemodialysis catheters. Issue 1 (6th October 2022) - Boucley, Isabelle; Dargent, Auguste; Andreu, Pascal; Roudaut, Jean‐Baptiste; Aptel, François; Labruyère, Marie; Jacquier, Marine; Cransac, Amélie; Quenot, Jean‐Pierre
Abstract: Background: We conducted a systematic review of studies investigating lock solutions for use in non‐tunneled hemodialysis catheters. Methods: We searched PubMed and Cochrane databases from inception to June 11, 2021. Study inclusion criteria were: randomized trial or observational study, adults (>18 years), with acute kidney injury (AKI); and temporary non‐tunneled catheters. We recorded bleeding events, catheter dysfunction and complications. Results: Of 649 studies identified, 6 were included (4 randomized, 1 non‐randomized trial, 1 retrospective cohort study; sample sizes 78–1496 patients). Citrate was compared to heparin in 4 studies, to saline in 1, and ethanol versus saline in 1. Event‐free survival of non‐tunneled catheters did not differ between groups. Catheter‐related infections and adverse events were less frequent with citrate locks, but reached statistical significance in only two studies. Conclusion: Existing data are too heterogeneous to enable recommending one type of catheter lock over any other for non‐tunneled hemodialysis catheters.